Seasonal iron fluxes and iron cycling in sandy bioirrigated sediments - Swenson Perger, Darci A.; Dwyer, Ian P.; Aller, Robert C.; Volkenborn, Nils; Heilbrun, Christina; Wehrmann, Laura M. (Frontiers in Marine Science, 2023)
Permeable sediments, which represent more than 50% of the continental shelves, have been largely neglected as a potential source of Fe in current global estimates of benthic dissolved iron (Fed) fluxes. There are open questions regarding the effects of a range of factors on Fed fluxes from these deposits, including seasonal dynamics and the role of bioirrigation. To address these gaps, we performed laboratory-based sediment incubation experiments with muddy sands during summer (21 °C) and winter (7 °C). We used bioirrigation mimics to inject overlying water into the permeable sediment with patterns resembling the bioirrigation activity of the prolific bioturbating polychaete, Clymenella torquata. Newly developed in-line Fe accumulators were used to estimate Fe fluxes with a recirculating set-up. We found high Fed fluxes from sandy sediments, especially in benthic chambers with simulated bioirrigation. In the winter fluxes reached >200 µmol Fed m-2 d-1 at the onset of irrigation and then decreased over the course of a 13-day experiment while in the summer fluxes from irrigated sediments reached >100 µmol Fed m-2 d-1 and remained high throughout a 7-day experiment. Despite different geochemical expressions of Fe-S cycling and resulting porewater Fed concentrations in winter and summer, large Fed fluxes were sustained during both seasons. Solid-phase and porewater concentration profiles showed that maximum concentrations of key constituents, including total solid-phase reactive Fe, and porewater Fed and ammonium, were located closer to the sediment water interface (SWI) in irrigated cores than in non-irrigated cores due to the upward advective transport of dissolved porewater constituents. This upward transport also facilitated Fed fluxes out of the sediments, especially during times of active pumping. Our study demonstrates the potential for large Fed fluxes from sandy sediments in both summer and winter, despite relatively low standing stocks of labile organic matter and porewater Fed. The primary driver of these high fluxes was advective porewater transport, in our study induced by the activity of infaunal organisms. These results suggest that permeable sediments, which dominate shelf regions, must be explicitly considered in global estimates of benthic Fed fluxes, and cannot be simply extrapolated from estimates based on muddy sediments.